Strengthening Independence: Constitutional Interests As A Paradigm For Judicial Review In Indonesia - Rahman, Andriansyah; Maizaroh, Muthi'ah (Jurnal Hukum dan Peradilan, 2024)
The existence of a constitutional injury requirement since Constitutional Court Decision Number 006/PUU-III/2005 was strengthened by Constitutional Court Regulation Number 2 of 2021. In fact, 34 cases in the last 3 years have been ruled inadmissible due to the issue of not fulfilling the requirements of constitutional injury. Some of them are about the New Criminal Code and the Law on Villages, which are considered urgent to be tested but are hampered by the fulfillment of the constitutional injury requirement. This research will prove that the constitutional injury requirement has distorted the independence of the Indonesian Constitutional Court. On the other hand, constitutional interests is a paradigm for restoring the independence, analyst and comparison have provided answers to the issues raised. The results of normative legal research with literature study show two important things. First, the requirement of constitutional injury undermines independence, so it must be eliminated and accompanied by a supporting paradigm that allows it to be eliminated. Second, applying the paradigm of constitutional interests as a condition for fulfilling legal standing. Systematically, constitutional interests are a manifestation of the independence of the Indonesian Constitutional Court by removing obstacles for the public to achieve access to justice.